A new species of Hemiphyllodactylus (Squamata, Gekkonidae) from western Yunnan, China - Hongxin Zhou; Xiaohan Wang; Liangwei Cui; Dongru Zhang; Ziqi Shen; Xiuyan Li; Shuo Liu; Dingqi Rao (Zoosystematics and Evolution)
A new species of gekkonid, Hemiphyllodactylus laowozhenensis sp. nov., is described based on three specimens from Lushui City, Yunnan, China. The new species can be distinguished from its congeners by a significant genetic divergence of greater than 4.8% in the mitochondrial ND2 gene and a combination of the following characters: maximum SVL of 38.5 mm; 10 or 11 chin scales; enlarged postmentals; 6 circumnasal scales; 2 or 3 internasal scales; 8 or 9 supralabial scales; 8 or 9 infralabial scales; 15 or 16 dorsal scales; 9 ventral scales; a manual lamellar formula of 3-4-4-4 and a pedal lamellar formula of 3(4)-4-4-4; 26–28 precloacal and femoral pore-bearing scales contiguous in males; 1–3 cloacal spur on each side; a dark postorbital stripe extending to at least base of neck; dorsolateral light–colored spots on trunk present; dark ventrolateral stripe on trunk present; dark dorsal transverse blotches present; and a dark and brown postsacral mark bearing anteriorly projecting arms.